RETRACTED: Trends in the artificial intelligence market of the Russian Federation - Gurianov Artem; Gurianova Elina; Gurianov Vadim (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001